Safety and effectiveness of the SUPRACOR presbyopic LASIK algorithm on hyperopic patients. Issue 1 (December 2016) - Ang, Robert; Cruz, Emerson; Pisig, Alex; Solis, Maria; Reyes, Rosalie; Youssefi, Gerhard
Abstract Background To evaluate the safety and effectiveness of the Supracor excimer laser algorithm to treat hyperopic presbyopic patients using laser in-situ keratomileusis (LASIK). Methods This is a retrospective case review of patients diagnosed with hyperopia (Sphere ≥ +0.0 D and presbyopia reading add ≥ 1.0 D) who underwent Supracor excimer laser treatment on at least one eye for presbyopia correction from year May 2011 to May 2013. Binocular vision was further analyzed after patients were subdivided into three groups: Group A (n = 22 eyes, 11 patients) had Supracor on both eyes; Group B (n = 18 eyes, 18 patients) had Supracor in one eye and hyperopic LASIK on fellow eye; and Group C (n = 29 eyes, 29 patients) had Supracor in one eye and no treatment on the fellow eye. Results This study evaluated 58 patients wherein 69 eyes underwent Supracor presbyopic LASIK. Preoperatively, mean manifest refraction spherical equivalent (MRSE) of all eyes that underwent Supracor was +1.37 ± 0.72 D with mean uncorrected distance visual acuity (UDVA), uncorrected intermediate visual acuity (UIVA), and uncorrected near visual acuity (UNVA) of 20/50 (0.35 logMAR), 20/50 (0.35 logMAR), and J9 (0.61 logMAR), respectively. At 6 months postoperatively, mean MRSE was −0.43 ± 0.59 D with mean UDVA, UIVA and UNVA of 20/25 (0.13 logMAR), 20/20 (0.01 logMAR), and J1 (0.05 logMAR), respectively. Loss of two lines of best-corrected distance visual acuity (BCDVA) was seen in 6% of eyes. Mean corneal steepening of 1.0 D at the 3 mm zone and 0.7 D in the 5 mm zone was observed. Mean vertical coma increased from −0.02 to +0.10 while mean 4th order spherical aberration became more negative from 0.20 to −0.14. Mean binocular UDVA, UIVA, and UNVA are 20/20, 20/20 and J1, respectively, in all treatment groups at the 6 month postoperative follow-up. No significant differences in binocular UDVA (p ≥ 0.36), UIVA (p ≥ 0.19) and UNVA (p ≥ 0.56) among groups were seen. Conclusions Supracor excimer laser algorithm is safe and effective for the treatment of presbyopia in hyperopes. Monolateral and bilateral Supracor treatments yielded similarly good binocular vision outcomes.